Central airway obstruction - Guedes, Fernando (2022)
Funding: This research was supported by Projects PEst-OE/AGR/UI0211/2011 from FCT, and COMPETE 2020, from ANI – Projetos ID&T Empresas em Copromoção, by the project “insitu.Biomas – Reinvent biomanufacturing systems by using an usability approach for in situ clinic temporary implants fabrication” with the reference POCI-01-0247-FEDER-017771, by the project “Print-on-Organs – Engineering bioinks and processes for direct printing on organs” with the reference POCI-01-0247-FEDER-033877, and by the project “Bone2Move – Development of “in vivo” experimental techniques and modelling methodologies for the evaluation of 4D scafolds for bone defect in sheep model: an integrative research approach” with the reference POCI-01-0145-FEDER-031146. Mariana Vieira Branquinho (SFRH/BD/146172/2019), Ana Catarina Sousa (SFRH/BD/146689/2019), and Rui Damásio Alvites (SFRH/BD/116118/2016), acknowledge FCT, for financial support.